ARK 2012: AWI airborne Accumulation radar data in Northern and Souther central Greenland over NEEM, NorthGRIP, and EGRIP deep ice core drill sites (Structure NGT 2012 project) - Heinrich Miller; Daniel Steinhage; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI Accumulation radar system (ACCU; Janett, M.& Steinhage, D., 2012) during the Arctic season of 2012. The profiles extend across northern central Greenland over NEEM, NorthGRIP, and EGRIP deep ice core drill sites as well as southern Greenland. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.